2017
DOI: 10.11648/j.ejcbs.20170304.11
|View full text |Cite
|
Sign up to set email alerts
|

Non-Steroidal Anti-Inflammatory Drugs and Vitamin C in the Rotenone Induced Nigrostriatal Damage in Mice

Abstract: Abstract:The nigrostriatal pathway is a dopaminergic pathway that connects the substantia nigra with the dorsal striatum.Loss of dopamine neurons in the substantia nigra is one of the main pathological features of Parkinson's disease, leading to a marked reduction in dopamine function in this pathway. This study aimed at evaluating the protective role of two antiinflammatory drugs, indomethacin and nimesulide separately or in combination with vitamin C against biochemical disturbances, brain damage and motor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 73 publications
(93 reference statements)
1
5
0
Order By: Relevance
“…Rotenone also caused a significant increase in brain nitric oxide, a finding that is in agreement with previously published observations [33][34][35]. We have also shown that rotenone resulted in increased nitric oxide release and prominent inducible nitric oxide synthase (iNOS) immunostaining in the striatum and SNpc [33][34][35]59].…”
Section: Rossupporting
confidence: 92%
See 4 more Smart Citations
“…Rotenone also caused a significant increase in brain nitric oxide, a finding that is in agreement with previously published observations [33][34][35]. We have also shown that rotenone resulted in increased nitric oxide release and prominent inducible nitric oxide synthase (iNOS) immunostaining in the striatum and SNpc [33][34][35]59].…”
Section: Rossupporting
confidence: 92%
“…There were also α-synuclein-like deposits in the remaining SNpc neurons [29,49]. Other studies have shown that rotenone given to mice via subcutaneous or intragastric routes was capable of inducing nigrostriatal degeneration [31][32][33][34][35]52]. The mouse model of rotenone administration was used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations